The Selection of Groundwater Recharge Sites in the Arid Region of Northern Badia, Jordan, using GIS-Based Multicriteria Decision Analysis - Al-Shabeeb, Abdel Rahman (Geological Agency, 2018)
DOI: 10.17014/ijog.5.3.199-209This study aims to locate new groundwater recharge sites in the arid region of northern Badia, Jordan, based on specific criteria including lithology, drainage and lineament density, soil texture, slope, and rainfall. With groundwater serving as the key source of Jordanian drinking water, the use of surface water for groundwater recharge is essential in maximizing the groundwater available. Groundwater recharge sites were selected using the weighted linear combination (WLC) method with the aforementioned criteria. According to the findings, 5.064% of the region is very highly suited to groundwater recharge, 33.599% of the region is highly suited, and 3.789% of the region is moderately suited. However, 26.634% of the region is poorly suited to groundwater recharge, with a further 30.943% being very poorly suited. The significance of each criterion for groundwater recharge was identified using removal analysis, with the most significant factor being efficient groundwater management. Given this finding, big data are required in order to determine the optimal locations for groundwater recharge as part of future groundwater planning and management.